Plasmon-induced photoelectrocatalytic activity of Au nanoparticles enhanced TiO2 nanotube arrays electrodes for environmental remediation - Wu, Ling; Li, Fang; Xu, Yuanyuan; Zhang, Jane W.; Zhang, Dieqing; Li, Guisheng; Li, Hexing (Applied catalysis. B, Environmental, 2015)
•Au nanoparticles enhanced TiO2 nanotube arrays.•Uniformly dispersed Au nanoparticles.•Plasmon-induced photoelectrocatalytic performance.•Enhanced photoelectrocatalytic activity for environmental remediation. A pulse electrodeposition (PED) technique was adopted to construct highly dispersed Au nanoparticles (Au-NPs) on TiO2 nanotube arrays (TiO2-NTs) electrodes prepared by electrochemical anodic oxidation. Both the particle size and loading amount were facilely controlled via adjusting electrochemical parameters. The morphology, crystallinity, elemental composition and light absorption capability of as-obtained Au/TiO2-NTs were distinguished based on various characterizations. Compared with pure TiO2-NTs, Au/TiO2-NTs electrodes exhibited much higher photocurrent density and greatly enhanced photoelectrocatalytic (PEC) activity towards the degradation of methyl orange (MO) under visible-light irradiation (λ>420nm). The synergy effect between nanotubular structures of TiO2 and uniformly dispersed Au nanoparticles, as well as the small bias potential and strong interaction between Au and TiO2, facilitated the Au plasmon-induced charge separation and transfer, which lead to highly efficient and stable visible-light PEC activity.